Sulfur Regulates the Trade-Off Between Growth and Andrographolide Accumulation via Nitrogen Metabolism in Andrographis paniculata - Jian, Shao-Fen; Huang, Xue-Jing; Yang, Xiao-Nan; Zhong, Chu; Miao, Jian-Hua (Frontiers in Plant Science, 2021)
Nitrogen (N) and sulfur (S) are essential mineral nutrients for plant growth and metabolism. Here, we investigated their interaction on plant growth and andrographolide accumulation in a medicinal plant Andrographis paniculata grown at different N (4 mmol·L-1 and 8 mmol·L-1) and S levels (0.1 mmol·L-1 and 2.4 mmol·L-1). We found that increasing S application rate enhanced accumulation of andrographolide compounds (AGs) in A. paniculata. Simultaneously, salicylic acid (SA) and gibberellic acid 4 (GA4) were increased but trehalose/trehalose 6-phosphate (Tre/Tre6P) were decreased by high S, suggesting that they were involved in S-mediated accumulation of AGs. However, S affected plant growth differentially at different N levels. Metabolite analysis revealed that high S induced increases of TCA cycle and photorespiration at low N condition, which promoted N assimilation and S metabolism and simultaneously increased carbohydrate consumption and inhibited plant growth. In contrast, high S reduced N and S concentrations in plants and promoted plant growth at high N conditions. Taken together, our results indicated that increasing S application rate is an effective strategy to improve AGs accumulation in A. paniculata. Nevertheless, the interaction of N and S affected the trade-off between plant growth and AGs accumulation, in which N metabolism plays a key role.